Central Aortic Pressure and Arterial Stiffness in Parkinson’s Disease: A Comparative Study - Mehmet Balal; Meltem Demirkiran; Saime Paydas (Parkinson's Disease)
Background. Cardiovascular autonomic dysfunction, which leads to hemodynamic disorders, is commonly observed in patients with Parkinson’s disease (PD). Central aortic pressure (CAP) is the systolic blood pressure (SBP) at the root of the aorta. In young people, CAP is lower than peripheral arterial blood pressure. In older people, the difference between CAP and peripheral arterial blood pressure decreases depending on the extent of arterial stiffness (AS). In patients with AS, CAP increases. CAP is thus regarded as an indicator of AS. Objective. To compare CAP and other hemodynamic parameters for AS between patients with Parkinson’s disease and control group. We also aimed to evaluate changes in these hemodynamic parameters after the levodopa (LD) intake. Methods. We included 82 patients with PD and 76 healthy controls. Age, sex, disease duration, disease subtype, Hoehn–Yahr stage (H&Y), and nonmotor symptoms (NMS) were documented. TensioMed Software v.3.0.0.1 was used to measure CAP, peripheral arterial blood pressure, pulse pressure (PP), heart rate (HR), mean arterial pressure (MAP), augmentation index (AI), pulse wave velocity, and ejection time. All patients were being treated with LD, and measurements were performed 1 h before and 1 h after LD intake. Results. Baseline peripheral arterial blood pressure and CAP values were significantly higher in the PD group than in the control group (p<0.001 and p=0.02, respectively). Most cardiac hemodynamic parameters, including peripheral arterial blood pressure and CAP, decreased significantly (p<0.02 and p<0.001, respectively) after LD intake in the PD group. Disease subtype, duration, and severity did not affect any of the hemodynamic parameters. When NMS were evaluated, patients with psychosis and dementia showed higher baseline parameters. Conclusion. Loss of postganglionic noradrenergic innervation is well-known with PD. Several cardiac hemodynamic parameters were affected, suggesting cardiac autonomic dysfunction in these patients. The data obtained were independent of disease severity, duration, and subtype. After LD intake, most of these parameters decreased, which might have a positive effect on the vascular burden.